Narrative revisited : telling a story in the age of new media - Hoffmann, Christian R.; Bublitz, Wolfram (Pragmatics & beyond, 2010)
The volume examines the role of narratives in old and new media. Its ten contributions firstly center on the various forms and functions narratives assume in computer-mediated environments, e.g. websites, weblogs, message boards, etc. In this light, past and present approaches to the description of narratives are presented and reevaluated based on their ability to capture the conceptual and methodological exigencies of new media. Secondly, the volume sheds new light upon the multimodal composition of new media narratives which typically feature multiple co-occurring semiotic modes such as spee.